Pendekatan Strategis dalam Penanganan Perilaku Anak Tunalaras pada PAUD Inklusi - Zahwa, Najwa Putri; Setiyatna, Hery (Center for Gender and Children Studies, Lembaga Penelitian dan Pengabdian Masyarakat (LP2M) UIN Sultan Thaha Saifuddin Jambi, 2025)
The phenomenon of emotional and behavioural difficulties in children, characterized by emotional instability and challenges in social interactions, requires systematic handling strategies based on the individual needs of the child. This study aims to identify and describe strategic approaches in managing the behaviour of children with emotional and behavioural disorders at PAUD Inklusi Saymara. The research methods were conducted through in-depth interviews, documentation, and literature review. The findings reveal that behaviour management strategies are implemented through synergy between teachers, parents, and therapists, supported by the application of structured daily routines, healthy eating patterns, and proper rest schedules for children. The implementation of these strategies has been proven to improve emotional stability, concentration in learning, and self-regulation abilities. Nevertheless, the study found obstacles in the form of low consistency of support at home and suboptimal parental involvement. Therefore, the sustainability of the strategy requires cross-environment coordination and strengthening the role of the family as a partner in inclusive education.